Development of a Teaching Module Based on Ethnomathematics for Class VIII on Two-Dimentional Figure Material - Qomariyah, Dinda Nurul; Sunardi, Sunardi; Yudianto, Erfan; Pambudi, Didik Sugeng; Rasyid, Irwan Hainur; Sukartini, Sukartini (Kreano, Jurnal Matematika Kreatif-Inovatif, 2024)
This research was motivated by students' difficulties in understanding mathematical concepts in the material of quadrilaterals and triangles. Therefore, researchers developed a teaching module to make it easier for students to understand mathematical concepts that suit student characteristics based on the ethnomathematics of typical batik found in the school environment. The aim of this research is to develop ethnomathematics-based teaching modules that are valid, practical, and effective. This research uses the Plomp development model. The subjects used in the trial class were class VIII B SMPN 1 Arjasa, using the random sampling method. Based on the results of the research analysis, it can be concluded that: 1) The ethnomathematics-based teaching module developed is valid, practical, and effective; 2) The teaching module that has been developed can help students understand the concept of flat shapes with a student completion percentage of 83.33% as well as student responses who are interested and happy to use the teaching module. The teaching module that has been developed can be used in mathematics learning for class VII middle school. Penelitian ini dilatarbelakangi oleh kesulitan siswa dalam memahami konsep matematika pada materi segiempat dan segitiga. Oleh karena itu, peneliti mengembangkan modul ajar untuk memudahkan siswa dalam memahami konsep matematika yang sesuai dengan karakteristik siswa berdasarkan etnomatematika khas batik yang terdapat di lingkungan sekolah. Tujuan penelitian ini adalah untuk mengembangkan modul ajar berbasis etnomatematika yang valid, praktis, dan efektif. Penelitian ini menggunakan model pengembangan Plomp. Subyek yang digunakan pada kelas uji coba adalah kelas VIII B SMPN 1 Arjasa, dengan menggunakan metode random sampling. Berdasarkan hasil analisis penelitian dapat disimpulkan bahwa: 1) Modul ajar berbasis etnomatematika yang dikembangkan valid, praktis dan efektif; 2) Modul ajar yang dikembangkan dapat membantu siswa dalam memahami konsep bangun datar dengan persentase ketuntasan siswa sebesar 83,33% serta respon siswa yang tertarik dan senang menggunakan modul ajar. Modul ajar yang dikembangkan dapat digunakan dalam pembelajaran matematika kelas VII SMP.